National Vote Intention and European Voting Behavior, 1979-2004: Second Order Election Effects, Election Timing, Government Approval and the Europeanization of European Elections - Philip Manow (Max Planck Institute for the Study of Societies, 2005)
Voting behavior in elections to the European Parliament seems to follow a regular pattern, as many EP-election studies have found: Parties in government at the national level tend to lose vote shares in EP-elections as compared to the last domestic electoral contest; small and ideologically more extreme parties tend to gain vote shares. These losses and gains seem to be more pronounced when the European election is held in the middle of the domestic legislative term (mid-term effect). In the many accounts that try to explain these regular deviations from domestic voting, one causal factor plays a central role: the popularity loss of parties in office at the national level. Since reliable and comparable popularity data for the EU-member states seems to be missing, the literature has attempted to measure popularity loss with two kinds of proxies: changes in economic performance (e.g. changes in the unemployment rate) and the timing of the EP-election within the domestic term. This paper proposes to use the bi-annually collected national vote intention question of the Eurobarometer surveys as a measurement for party popularity. The paper has three central findings: 1) changes in national vote intention are a strong and stable predictor for the actual vote share shifts between national and European elections, 2) neither the economic nor the election timing variables contribute substantially to the explanation of the vote share shifts; 3) changes in the impact of the national vote intention variable on European election outcomes over the six EPelections held so far suggest that the European electorates have taken European issues more and more into consideration when participating in European elections (Europeanization of EPelections). However, the data also suggests that voters have used these elections increasingly to voice their dissatisfaction with the European integration process (Anti-Europeanization of EPelections). – – Das Stimmverhalten in den Direktwahlen zum europäischen Parlament folgt einem Muster, das in der Literatur bereits ausführlich beschrieben worden ist. Regierungsparteien verlieren Stimmenanteile im Vergleich zur vorangegangenen nationalen Wahl, kleine Parteien und ideologisch extremere Parteien gewinnen hingegen Stimmenanteile hinzu. Diese relativen Stimmenverlusten beziehungsweise -gewinne scheinen ausgeprägter, wenn die Europawahl in die Mitte der nationalen Wahlperiode fällt (mid-term effect). In vielen der bislang für dieses Muster angebotenen Erklärungen ist ein Faktor von zentraler kausaler Bedeutung ? die (sinkende) Popularität der jeweiligen nationalen Regierungsparteien. Da es bislang für die EU-Mitgliedsländer keine verlässlichen und vergleichbaren Popularitätsdaten zu geben schien, half sich die Literatur damit, Popularität durch zwei "Proxies" zu messen: durch die Änderung zentraler ökonomischer Parameter (wie Arbeitslosigkeit) und durch die Datierung der Europawahl innerhalb der nationalen Legislaturperiode. Dieser Aufsatz schlägt vor, die halbjährlich erhobenen Wahlabsichts-Daten des Eurobarometers für die Ermittlung der Parteienpopularität zu verwenden. Ich zeige, dass 1) diese Variable sich in allen möglichen Modellspezifikationen als stabil erklärungskräftig für die tatsächlichen Stimmenverschiebungen in Europawahlen erweist, dass 2) die gängigen ökonomischen Variablen und die Zeitvariablen keinen stabilen Beitrag zur Erklärung der Stimmanteilsverschiebungen zwischen nationalen und europäischen Wahlen liefern, und dass 3) die über Zeit abnehmende Bedeutung der nationalen Wahlabsichts-Variable auf einen Prozess der Europäisierung der Europawahlen hinweist.
Keywords: 300